2014
DOI: 10.1042/cs20130828
|View full text |Cite
|
Sign up to set email alerts
|

Role of MIF in myocardial ischaemia and infarction: insight from recent clinical and experimental findings

Abstract: First discovered in 1966 as an inflammatory cytokine, MIF (macrophage migration inhibitory factor) has been extensively studied for its pivotal role in a variety of inflammatory diseases, including rheumatoid arthritis and atherosclerosis. Although initial studies over a decade ago reported increases in circulating MIF levels following acute MI (myocardial infarction), the dynamic changes in MIF and its pathophysiological significance following MI have been unknown until recently. In the present review, we sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 91 publications
2
48
1
Order By: Relevance
“…Previous studies demonstrated that following MI, MIF is immediately released from injured cardiomyocytes, providing predominately protective properties through its receptor, CD74, and its antioxidant capacity 27, 59, 60. In contrast, a second delayed wave of MIF derived from infiltrating immune cells contributes to aggravation of cardiac function and adverse cardiac remodeling, presumably mainly through CXCR2 and CXCR4 59.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrated that following MI, MIF is immediately released from injured cardiomyocytes, providing predominately protective properties through its receptor, CD74, and its antioxidant capacity 27, 59, 60. In contrast, a second delayed wave of MIF derived from infiltrating immune cells contributes to aggravation of cardiac function and adverse cardiac remodeling, presumably mainly through CXCR2 and CXCR4 59.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a second delayed wave of MIF derived from infiltrating immune cells contributes to aggravation of cardiac function and adverse cardiac remodeling, presumably mainly through CXCR2 and CXCR4 59. The recently discovered soluble CD74 ectodomain (sCD74) fragment expands the understanding about the complex interaction within the MIF protein family and necessitates to understand its role within the MIF/receptor network.…”
Section: Discussionmentioning
confidence: 99%
“…In the initial phase of ischemia, MIF promotes metabolic adaptation and recovery. With prolonged ischemia and myonecrosis, MIF’s proinflammatory actions supervene, resulting in detrimental effects on contractility, functional recovery, and ventricular remodeling [96]. …”
Section: Mif Family Proteins In Myocardial Infarction and Ischemia Rementioning
confidence: 99%
“…MIF has a range of actions, including metabolic regulation and modulation of inflammatory responses, and plays an important role in cardiovascular disease (CVD) . MIF is known to play a significant role in AMI and ischemia/reperfusion injury . Previous clinical studies by other groups reported an increase in plasma MIF levels in patients with AMI 4 to 6 hours after admission .…”
Section: Introductionmentioning
confidence: 99%